Herbert Moritz Caro: exílio e vida no Brasil - Kestler, Izabela Maria Furtado (Contingentia, 2008)
This article offers a general view on the historical circumstances regarding the exile of Herbert Caro in Brazil. It also informs on his intellectual and professional background, based on official documents and research material as well as on an interview that the author realized with Herbert Caro in 1988.